2020
DOI: 10.1186/s12711-020-0523-1
|View full text |Cite
|
Sign up to set email alerts
|

Genomic regions associated with muscularity in beef cattle differ in five contrasting cattle breeds

Abstract: Background: Linear type traits, which reflect the muscular characteristics of an animal, could provide insight into how, in some cases, morphologically very different animals can yield the same carcass weight. Such variability may contribute to differences in the overall value of the carcass since primal cuts vary greatly in price; such variability may also hinder successful genome-based association studies. Therefore, the objective of our study was to identify genomic regions that are associated with five mus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 68 publications
2
24
0
Order By: Relevance
“…Furthermore, some of the top 140 QTLs were also previously associated with carcass weight (McClure et al, 2010;Saatchi et al, 2014a) and residual feed intake (Nkrumah et al, 2007;Lu et al, 2013;Saatchi et al, 2014a) in cattle. Nineteen QTLs identified in the present study have also been identified previously as being associated with linear type traits describing the muscular characteristics of cattle (Doyle et al, 2020).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Furthermore, some of the top 140 QTLs were also previously associated with carcass weight (McClure et al, 2010;Saatchi et al, 2014a) and residual feed intake (Nkrumah et al, 2007;Lu et al, 2013;Saatchi et al, 2014a) in cattle. Nineteen QTLs identified in the present study have also been identified previously as being associated with linear type traits describing the muscular characteristics of cattle (Doyle et al, 2020).…”
Section: Discussionsupporting
confidence: 71%
“…This indicates the existence of breed-specific and trait-specific QTL for skeletal traits, which has implications for the usefulness of such QTL in across-breed genomic evaluations where only purebreds are used. Previous studies have documented both across-breed and breed-specific QTL associated with carcass traits, birth weight, weaning weight, and mature weight (Saatchi et al, 2014b), as well as dry matter intake, growth and feed efficiency (Saatchi et al, 2014a), carcass traits (Purfield et al, 2019), and muscular type traits (Doyle et al, 2020) in beef cattle. Excluding stature (Bouwman et al, 2018), the present study is the first published genome study on the skeletal linear type traits in beef cattle using imputed sequence data and is one of few genome-based studies comparing QTLs across multiple breeds of cattle.…”
Section: Discussionmentioning
confidence: 99%
“…A genome-wide association study in Holstein cattle discovered a significant SNP for milk yield located in the P4HA3 gene at 54.4 Mb on BTA15 [ 107 ]. Moreover, Doyle et al [ 108 ] reported suggestive SNPs for beef traits that are located in the CHRDL2 and NEU3 genes on BTA15. Beyond that, NEU3 was demonstrated to have functional effects on fertility and production traits in Holstein Friesian [ 109 ].…”
Section: Discussionmentioning
confidence: 99%
“…This genomic region was also identified to harbor a selection signature for body weight in Korean breeds [ 35 ]. The gene TMEM178A was found to be suggestively associated with loin muscularity in multiple beef cattle breeds [ 36 ]. In the same region was the MAP4K3 gene, involved in the Trypanosome resistance of the N’Dama cattle [ 37 ].…”
Section: Resultsmentioning
confidence: 99%